Takagi-Sugeno Model-Based Control with Observer Design for Disturbance Rejection and Input Constraints in Rotary Inverted Pendulum Systems - Ngoc-Linh Tao; Bao-Trung Dong; Thi-Van-Anh Nguyen (Journal of Applied Science and Engineering, 2026)
This paper proposes a Takagi-Sugeno (T-S) model-based control strategy for the Rotary Inverted Pendulum (RIP) system to address nonlinear dynamics, disturbance rejection, and input constraints. By utilizing the T-S fuzzy framework, the nonlinear system is approximated with a set of linear submodels weighted by membership functions, allowing the application of linear matrix inequality (LMI)-based techniques for controller and observer design. A robust observer is developed to estimate unmeasured states in real-time, enabling the controller to achieve performance comparable to full-state feedback systems, even under disturbances. The controller incorporates disturbance rejection mechanisms and explicitly enforces input constraints, ensuring stability. Simulation results demonstrate the effectiveness of the proposed strategy, achieving stabilization, accurate state estimation, and compliance with input constraints. These results confirm the potential of the T-S fuzzy framework as an efficient approach for controlling nonlinear systems like the RIP.